# If f(x) = 3x4 – 2x3 + 2x + 1. Find the value of f(1) – f(0).

Concept Used:

For a polynomial, f(1) equals to the value of f(x) when x = 1.

Explanation:

f(x) = 3x4 – 2x3 + 2x + 1

f(1) = 3(1)4 – 2(1)3 + 2.1 + 1 = 3 – 2 + 2 + 1 = 4

f(0) = 3(0)4 – 2(0) + 2. 0 + 1 = 1

f(1) – f(0) = 4 – 1 = 3

Hence, f(1) – f(0) = 3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz | Polynomials29 mins
Methods to find zeroes of a Polynomial-246 mins
Remainder Theorem and Factor Theorem38 mins
Polynomials - Zero to Hero42 mins
Genius Quiz | Polynomials40 mins
Zeros and Degrees of a Polynomial41 mins
Introduction to Polynomials37 mins
Quiz | Imp. Qs. on Algebraic Identities65 mins
Basic understanding of Polynomials37 mins
Genius Quiz | Division of Algebraic Expressions37 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

The zeroes of the polynomial p (x) = x2 + x - 6 are

RS Aggarwal & V Aggarwal - Mathematics

Zero of the polynomial p(x) = 2x + 3 is

RS Aggarwal & V Aggarwal - Mathematics

If find

(i) f (0)

(ii) f (4)

(iii) f (-5)

RS Aggarwal & V Aggarwal - Mathematics

If (x + 1) is a factor of 2x2+ kx, then k =?

RS Aggarwal & V Aggarwal - Mathematics

If (x2+ kx – 3) = (x – 3 ) (x + 1) then k =?

RS Aggarwal & V Aggarwal - Mathematics

The zeroes of the polynomial p (x) = x2 – 3x are

RS Aggarwal & V Aggarwal - Mathematics

The zeroes of the polynomial p (x) = 3x2 – 1 are

RS Aggarwal & V Aggarwal - Mathematics